Rethinking resistance: public health professionals on empathy and ethics in the 2014-2015 Ebola response in Sierra Leone and Liberia. Issue 5 (19th October 2020) - Walker, Alexis; Kennedy, Caitlin; Taylor, Holly; Paul, Amy
ABSTRACT: Public health professionals may be confronted with unique ethical challenges in outbreak response situations. We conducted interviews with twenty-two public health professionals involved in responses to the 2014–2015 Ebola epidemic in Sierra Leone and Liberia to explore how they understood and experienced the ethical challenges involved in this work. The concerns covered in these interviews ranged dramatically, but three themes emerged as unique contributions from a subset of individuals integrally involved with the frontline response, who framed concerns about representation as key ethical issues. These included concerns regarding misrepresentations of West Africans as 'resistant' to the epidemic response, failures in material and information resources provided in the response, and representations of 'rationality' between responders and publics. Such concerns suggest that perspectives advanced in the critical public health literature in recent decades are circulating amongst public health professionals involved in outbreak response, although discord amongst respondents suggests the need for more deliberate efforts to reframe thinking about resistance, resources, and rationality in future public health outbreak responses.